A Quantitative Analysis of Reading Comprehension in University Students - Ryan Al Ihsan; Yeni Rahmawati (Borneo Educational Journal (Borju), 2024)
This study was to investigate the correlation between students’ cognitive reading strategies and students’ reading comprehension. The population in this study were overall second-semester students of UMKT from all undergraduate faculty. The total population in the study was 2,362 students. The sampling that was chosen in this study was simple random sampling by selecting representative respondents from each study program. By using a table of sampling size with a confidence level of 95% (margin of error 0.05%), it was found that from N= 2362 total population, the total sample was 428 students. The conducting data found that there was a significant relationship (sign. 0.01) between cognitive strategy and reading comprehension among students at UMKT. It was proved from the result that the significant value was under the p-value (0.05). However, the level of correlation was small, it was because some respondents stated that they didn’t use their mother tongue or read aloud when they got a difficult text, and they used translator apps to get an instant way of understanding the texts. The suggestion for the next researchers and practitioners such as teachers is to use a cognitive strategy to understand English rather than using an instant way likewise using the application or asking someone else to get the answer or comprehension. In other words, cognitive strategies involve active engagement with the activity, which aids in comprehension meanwhile Reading comprehension is a cognitive ability that provides the ability to synchronize text information with background knowledge